2006
DOI: 10.1021/jp055515x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Mechanistic Study on the Radical−Molecule Reaction of CH2OH with NO2

Abstract: The complex singlet potential energy surface for the reaction of CH2OH with NO2, including 14 minimum isomers and 28 transition states, is explored theoretically at the B3LYP/6-311G(d,p) and Gaussian-3 (single-point) levels. The initial association between CH2OH and NO2 is found to be the carbon-to-nitrogen approach forming an adduct HOCH2NO2 (1) with no barrier, followed by C-N bond rupture along with a concerted H-shift leading to product P1 (CH2O + trans-HONO), which is the most abundant. Much less competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Computational studies on the isomers and isomerization channels of H 3 CNO 3 were found to be limited. For the reaction of CH 2 OH with NO 2 , theoretical exploration of the singlet PES was made at B3LYP/6‐311G(d,p) and G3 single point levels, and 14 EQ and 28 TS were reported . This is an outstanding study of H 3 CNO 3 , but it includes only limited parts of isomerization channels around nitromethanol 12 (HOCH 2 NO 2 ) and local species of 7 , 8 , 10 , 15 , and 18 .…”
Section: Remarks On the Present Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…Computational studies on the isomers and isomerization channels of H 3 CNO 3 were found to be limited. For the reaction of CH 2 OH with NO 2 , theoretical exploration of the singlet PES was made at B3LYP/6‐311G(d,p) and G3 single point levels, and 14 EQ and 28 TS were reported . This is an outstanding study of H 3 CNO 3 , but it includes only limited parts of isomerization channels around nitromethanol 12 (HOCH 2 NO 2 ) and local species of 7 , 8 , 10 , 15 , and 18 .…”
Section: Remarks On the Present Approachmentioning
confidence: 99%
“…This article describes a study on the exploration of isomers, isomerization reactions, as well as their reaction routes for H 3 CNO 3 using SHS‐ADDF. Studies on H 3 CNO 3 were reported recently in relation to combustion and atmospheric chemistry . The reaction channels for some isomers of H 3 CNO 3 including nitromethanol (HOCH 2 NO 2 ) and nitrosooxymethnol (HOCH 2 ONO) were elucidated using hybrid density‐functional‐theory (DFT) B3LYP method in connection with radical‐molecule reaction of CH 2 OH with NO 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxyalkyl radicals can advance various reactions with HO x . In fact, hydroxyalkyl radicals are a subclass of oxygenated carbon-centered free radicals that are produced as intermediates in various reaction sequences . The carbon-centered oxy radicals are thermodynamically more stable than the isomeric oxygen-centered alkoxy radicals .…”
Section: Introductionmentioning
confidence: 99%
“…The hydroxymethyl (CH 2 OH) radical is of interest to combustion chemists due to its importance in the combustion and atmospheric chemistry, as well as its capability to react with NO X species. Reactions of the CH 2 OH radical with NO 2 , , O 2 , hydrogen halides, H 2 O, H 2 O 2 , several saturated and unsaturated hydrocarbons, OH, and HO 2 , , have been studied by experiment or ab initio calculation. In the one previous experimental study of the kinetics of the title reaction, Pagsberg et al suggested two possible product channels: …”
Section: Introductionmentioning
confidence: 99%